A clinical assessment of periimplant marginal bone loss and soft tissue status in dental implant placed by flapless implant surgery. (A one-year prospective study) (Mustansiria Dental Journal, 2018)
Despite several studies have been conducted to evaluate the clinical outcomes offlapless implant surgery limited information presents regarding the clinical conditionsafter flapless implant surgery, for this reason this study was carried out to evaluate theperi-implant marginal bone loss and soft tissue status in dental implant placed byflapless implant surgery.In the present study, 143 implants were placed in 68 patients by using a flapless 1-stage procedure. In these patients, peri-implant soft tissue conditions and radiographicmarginal changes were evaluated one year after surgery.Results: None of the implants was lost during follow-up, giving a success rate of100%. The mean score of GI was (0.28 mm SD = 0.21), the average BOP index was(0.12, SD= 0.05) and the mean pocket probing depth was (2.7 mm, SD= 1.1).The mean marginal bone loss (0,4 mm, SD = 0.49) range ( 0.0 – 1.2 mm ).Whereas 34 implants showed no bone loss at all.The results of this study demonstrate that flapless implant surgery is a predictableprocedure. In addition, it is advantageous for preserving crestal bone and mucosalhealth surrounding dental implants.